Parametric Analysis of Indium Gallium Arsenide Wafer-based Thin Body (5 nm) Double-gate MOSFETs for Hybrid RF Applications - Paramasivam, Pattunnarajam; Gowthaman, Naveenbalaji; Srivastava, Viranjay. M. (Recent Patents on Nanotechnology, 2024)
Introduction: The electrical behavior of a high-performance Indium Gallium Arsenide (In- GaAs) wafer-based n-type Double-Gate (DG) MOSFET with a gate length (LG1= LG2) of 2 nm was analyzed. The relationship of channel length, gate length, top and bottom gate oxide layer thickness, a gate oxide material, and the rectangular wafer with upgraded structural characteristics and the parameters, such as switch current ratio (ION/IOFF) and transconductance (Gm) was analyzed for hybrid RF applications. Methods: This work was carried out at 300 K utilizing a Non-Equilibrium Green Function (NEGF) mechanism for the proposed DG MOSFET architecture with La2O3 (EOT=1 nm) as gate dielectric oxide and source-drain device length (LSD) of 45 nm. It resulted in a maximum drain current (IDmax) of 4.52 mA, where the drain-source voltage (VDS) varied between 0 V and 0.5 V at the fixed gate to source voltage (VGS) = 0.5 V. The ON current(ION), leakage current (IOFF), and (ION/IOFF) switching current ratios of 1.56 mA, 8.490-6 μA, and 18.307 μA were obtained when the gate to source voltage (VGS) varied between 0 and 0.5 V at fixed drain-source voltage (VDS)=0.5V. Results: The simulated result showed the values of maximum current density (Jmax), one and twodimensional electron density (N1D and N2D), electron mobility (μn), transconductance (Gm), and Subthreshold Slope (SS) are 52.4 μA/m2, 3.607 cm-1, 11.36012 cm-2, 1417 cm2V-1S-1, 3140 μS/μm, and 178 mV/dec, respectively. The Fermi-Dirac statistics were employed to limit the charge distribution of holes and electrons at a semiconductor-insulator interface. The flat-band voltage (VFB) of - 0.45 V for the fixed threshold voltage greatly impacted the breakdown voltage. The results were obtained by applying carriers to the channels with the (001) axis perpendicular to the gate oxide. The sub-band energy profile and electron density were well implemented and derived using the Non-Equilibrium Green’s Function (NEGF) formalism. Further, a few advantages of the proposed heterostructure-based DG MOSFET structure over the other structures were observed. Conclusion: This proposed patent design, with a reduction in the leakage current characteristics, is mainly suitable for advanced Silicon-based solid-state CMOS devices, Microelectronics, Nanotechnologies, and future-generation device applications.
Keywords: NEGF